A Case of Infant-Type Hemispheric Glioma with NTRK1 Fusion. (December 2022) - Garcia, Mekka R.; Bell, Lena; Miller, Claire; Segal, Devorah
The incidence of childhood central nervous system tumors in infants is about 6 per 100 000 children. Recent studies have showed recurrent fusion of the neurotrophic tyrosine receptor kinase (NTRK) gene in 10% of non-brainstem high grade glioma in very young children suggesting an oncogenic effect of the NTRK fusion genes. In this report, we present a rare, severe case of a full-term neonate who was noted to have widely splayed sutures and a bulging fontanelle at birth who was found to have infant-type hemispheric glioma with NTRK1 fusion with course complicated by seizures refractory to medical treatment. Patient was deemed a poor surgical candidate due to the size of the mass and thus parents opted for comfort care.